Evaluation of EDTA induced pseudothrombocytopenia and the effect of alternative anticoagulants (Journal of Pathology of Nepal, 2014)
Background: Artifactual Thrombocytopenia is a condition in which there is falsely lowered platelet in patients who have thrombocytopenia but the absence of petechiae or echymoses. Pseudothrombocytopenia is also an artifactual thrombocytopenia caused by anticoagulant dependent agglutinins. The aim of this study was to compare the platelet count in pseudothrombocytopenia in EDTA anticoagulated samples and other alternative anticoagulants.Materials and methods: This study was performed in the department of hemotology hematology, Institute of medicine. All cases during study period were evaluated by EDTA-anticoagulated whole blood samples but criteria for selecting pseudothrombocytopenia patients was unexpectedly low platelet counts with clumping/aggregate on peripheral blood smear. Additional samples were collected in sodium citrate and heparin for examined.Results: A total of 50 patients aged between 18 to 90 years were found to have pseudothrombocytopenia. Platelet counts in samples anticoagulated with EDTA ranged from 20x109/l to 149x109/l and samples from same patients anticoagulated with citrate ranged from 41x109 /l to 312x109 /l and heparin showed platelet count ranging from 29x10 9 /l to 210x109 /l. The mean platelet count in EDTA- anticoagulated blood of individuals with pseudothrombocytopenia was 104x109/l whereas the mean platelet count in citrate and heparin-anticoagulated samples was 151x109/land123x109/l respectively. Platelet counts decreased dramatically in the EDTA samples in contrast to the samples anticoagulated with citrate or heparin post four hours of collection.Conclusion: Peripheral blood smears should be examined for platelet clumping/aggregates in cases with low platelet count not correlating with clinical presentation or in isolated thrombocytopenia flagged in hematology analyser. Alternative anticoagulants should be used for correct estimation of platelet count.DOI: http://dx.doi.org/10.3126/jpn.v4i8.11498 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 626-629